Hot Work: A Concerning Matters For Cadets (An Overview On Cadets As An Apprentice On Board Of A Ship) - Endah Fauziningrum; Lilik Budiyanto; Kundori Kundori (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
This study aims to examine why seafarers engage in simultaneous tasks, which may lead to accidents. In an exploratory qualitative study, face-to-face interviews were conducted with selective and targeted seafarers previously involved in maritime accidents. The collected data were analysed using interpretive and descriptive qualitative methods with a socio-cultural approach. The findings of this study show that the substantial regulatory changes over the years in the maritime industry have resulted in increased occupational workload for seafarers. Some of these regulatory barriers designed to improve safety at sea prompted seafarers to engage in simultaneous tasks to perform excessive paperwork and compensate for insufficient crewing. The research also revealed how a poor speak-up culture onboard might encourage simultaneous tasks leading to accidents at sea. The analysis shows that reasons for engaging in simultaneous tasks at sea are varied and complex. Therefore, complex intervention efforts to discourage seafarers from engaging in simultaneous tasks is needed to mitigate accidents at sea.